CONNECTION OF CULTURE AND LANGUAGE. (E Conference Zone, 2022)
A person learning any language also studies the language's national characteristics, traditions, and cultures. A person who knows multiple languages is considered to have mastered a nation's or people's culture. Because language exists exclusively in the context of nationality and culture. This article discusses the characteristics of the language-culture link as well as the perspectives of different linguists